2015
DOI: 10.1155/2015/891972
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation in Duchenne Muscular Dystrophy: Association with Muscle Function and Nutritional Status

Abstract: Inflammation described in patients with Duchenne muscular dystrophy (DMD) may be related to loss of muscle function or to obesity. It is unknown if circulating proinflammatory cytokines (IL-6, IL-1, and TNF-α) levels are associated with muscle function. The purpose was to evaluate whether an association exists between systemic inflammation with muscle function and nutritional status in DMD patients. In 66 DMD patients without corticosteroid treatment, the following were evaluated in serum: cytokines (IL-1, IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
0
4

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 28 publications
2
68
0
4
Order By: Relevance
“…; Cruz‐Guzmán et al . ; Pelosi et al . ) and is of particular relevance due to its role as a myokine and muscle signalling molecule.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Cruz‐Guzmán et al . ; Pelosi et al . ) and is of particular relevance due to its role as a myokine and muscle signalling molecule.…”
Section: Discussionmentioning
confidence: 99%
“…During the years of ambulation, plasma cytokine levels appear to be near maximal in DMD boys and begin to decline thereafter when patients become non‐ambulatory (Cruz‐Guzmán et al . ), perhaps due to the disuse of the lower limb musculature. IL‐6 is one of many cytokines reported to be elevated in DMD (Rufo et al .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the lack of functional dystrophin inevitably compromises the structure of the sarcolemma membrane, thus causing progressive muscle damage and failure (Matsumura et al, ). The inflammatory response, activation of necrosis and exhaustion of regeneration cycles of muscle fibres are all known mechanisms leading to the exacerbation of the disease (Cruz‐Guzmán et al, ; Miyatake et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, chronic inflammation decreases muscular regeneration, aggravating the loss of muscle function, as we proposed in patients with DMD. It has been observed that in boys who have more advanced disease are nonambulatory, and inflammatory markers such as interleukin‐1 (IL‐1), TNF‐α, and C‐reactive protein (CRP) are lower compared with ambulatory boys with earlier‐onset disease . Loss of muscle function is associated with a reduction in bone density, because bone is controlled by muscle strength .…”
mentioning
confidence: 99%
“…It has been observed that in boys who have more advanced disease are nonambulatory, and inflammatory markers such as interleukin-1 (IL-1), TNF-α, and C-reactive protein (CRP) are lower compared with ambulatory boys with earlier-onset disease. 11 Loss of muscle function is associated with a reduction in bone density, because bone is controlled by muscle strength. 10,12 Therefore, the loss of ambulatory function and muscle mass can lead to bone loss, as observed in children with DMD.…”
mentioning
confidence: 99%